2001
DOI: 10.1164/ajrccm.164.10.2102104
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Nasal Cannula Pressure Recordings for Assessment of Ventilation during Sleep

Abstract: Nasal prong pressure monitoring (PNOSE) is utilized to assess ventilation during sleep. However, it has not been rigorously validated against the gold standard of face-mask pneumotachography (VFM). Therefore, we compared PNOSE with VFM in 20 patients with suspected sleep apnea during nocturnal polysomnography, and analyzed factors affecting accuracy of PNOSE-derived variables. Patients rated their nasal obstruction on a visual analog scale. Mean +/- SE apnea/hypopnea index (AHI) by VFM was 24.0 +/- 5.1 h(-1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 15 publications
1
96
0
4
Order By: Relevance
“…Recordings were visually analyzed by review of the raw data on a computer video screen. An episode of apnoea or hypopnoea was defined as a decrease in the sum signal of the respiratory inductive plethysmograph to %50% of baseline for more than 10 s. We have previously shown that the apnoea/hypopnoea-index (AHI), calculated as the number of apnoeas/hypopnoeas per hour, determined by this technique agrees closely with facemask pneumotachography (19). Central apnoea was differentiated from obstructive apnoea/hypopnoea by the absence of chest-wall motion during the event (20).…”
Section: Measurementsmentioning
confidence: 75%
“…Recordings were visually analyzed by review of the raw data on a computer video screen. An episode of apnoea or hypopnoea was defined as a decrease in the sum signal of the respiratory inductive plethysmograph to %50% of baseline for more than 10 s. We have previously shown that the apnoea/hypopnoea-index (AHI), calculated as the number of apnoeas/hypopnoeas per hour, determined by this technique agrees closely with facemask pneumotachography (19). Central apnoea was differentiated from obstructive apnoea/hypopnoea by the absence of chest-wall motion during the event (20).…”
Section: Measurementsmentioning
confidence: 75%
“…Receiver operating characteristic (ROC) curves were used to test the diagnostic accuracy of impedance signal analysis for the detection of sleep apnea syndrome at various AHI cutoffs. 14 Statistical significance was assumed at a value of PϽ0.05. All analyses were performed by use of a commercially available statistical package (SPSS for Windows 9.0).…”
Section: Discussionmentioning
confidence: 99%
“…They have been widely used in sleep studies and have been shown to be reliable and sensitive for detection of apnoea and hypopnea (Thurnheer, Xie, & Bloch, 2001). Nasal pressure measures of respiration have been shown to be comparable with facemask pneumotachography, which is the gold standard quantitative measurement for respiration in sleep (Thurnheer et al, 2001). They have also been shown to be more sensitive than thermocouples or thermistors to subtle changes in airflow and airway resistance, indicating the potential of pressure measurements for use in cough strength testing 1 .…”
Section: Cough Pressuresmentioning
confidence: 99%